Special Food Safety Issues during Pregnancy - Claudia Peñuela; Amy Simonne (EDIS)
FCS8886, a 2-page fact sheet by Claudia Peñuela and Amy Simonne, highlights special food safety issues for pregnant women: listeriosis, methylmercury, and toxoplasmosis. Includes references. Published by the UF Department of Family Youth and Community Sciences, December 2009.